Impact of the provision of school lunch on attendance in remote rural Jamaican primary schools. (January 2016) - Jennings, Zellynne
Highlights: Attendance rates in remote rural primary schools improved over a 10 year period. Conditional cash grants to parents contributed to the improvement in attendance. The attendance patterns of children who take different lunch types are similar. The inadequacy of supply of one lunch type has persisted for nearly two decades. School breakfasts are recommended to improve the school feeding programme. Abstract: This study examined the attendance patterns by region of schools which participated in School Feeding Programmes (SFPs) in poor, remote rural areas of Jamaica and determined whether there was a significant difference in attendance over a 10 year period between children who took different lunch types. The study revealed peaks and troughs in the average annual attendance by region, but found no significant difference in attendance by lunch type. Variations in poverty levels and the effect of a conditional cash grant to poor parents are offered as possible explanations for the peaks and troughs in attendance.